2021
DOI: 10.21203/rs.3.rs-847240/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myogenic differentiation potential of chicken mesenchymal stem cells from bone marrow

Abstract: Background: Mesenchymal stem cells (MSCs) have the potential to multilineage differentiation, which can be used for a good model to provide critical insight of chicken muscle development. Differential adhesion method is one of the commonest methods to isolate MSCs based on the ability of plastic adhesion. 5-azacytidine (5-Aza), dexamethasone (DXMS), hydrocortisone (HC) and horse serum had been proved the potential to induce the myogenic differentiation of MSCs. However, the myogenic differentiation of MSCs is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Chicken BM-MSCs have properties similar to mammalian MSCs. On the other hand, although the myogenic differentiation of chicken MSCs is still poorly understood, recently Zhou et al showed that chicken MSCs have the potential for myogenic differentiation by the treatment of dexamethasone (DEX), HC and horse serum, or 5-Aza and horse serum [105].…”
Section: Avian Mscs For Myogenic Differentiationmentioning
confidence: 99%
“…Chicken BM-MSCs have properties similar to mammalian MSCs. On the other hand, although the myogenic differentiation of chicken MSCs is still poorly understood, recently Zhou et al showed that chicken MSCs have the potential for myogenic differentiation by the treatment of dexamethasone (DEX), HC and horse serum, or 5-Aza and horse serum [105].…”
Section: Avian Mscs For Myogenic Differentiationmentioning
confidence: 99%